Ultrastructure of pancreatic endocrine cells of the single hump camel (Camelus dromedarius) - Bsoul, Manal Khalid; Qar, Janti Salahuddin; Al-Ani, Imad Matloub Dally; Al-Adhami, Mohammad Amin (Department of Anatomy, National University of Singapore, 2013)
The present study was undertaken to provide an ultrastructural identiﬁ cation of the different cells in the islets of the camel pancreas. Tissue samples were obtained from ten healthy, adult camels and processed for electron microscopy. The islets are composed of abundant, centrally located beta; β-cells, alpha; α-cells are present at the very periphery of the islets, while delta; δ-cells are distributed among both β- and α-cells. These cells were easily distinguished on the basis of the morphology of secretory granules. The granules of the β-cells varied greatly in shape and size and both “dense and pale” granules could be identiﬁ ed. The α-cells have a homogeneous rounded core of moderate to high electron density granules. The δ-cells contain large spherical to irregular shaped granules of variable electron density. Our ﬁ ndings of the single-humped camel pancreas make additional contribution to those found in other mammalian species.